The 1998 Crisis, Democratization and the "War and Terror" - M. Muttaqien, S.IP., MA., Ph.D (Cakra Studi Global Strategis, 2012)
This book offers a compilation of articles taken from papers presented by the author in several discussions, seminars, and published in journals. The issues which have been presented in this book are on the 1998 Asian Financial Crisis, Democratization in Indonesia and the “War on Terror” with the case of Indonesia and Japan. It will be discussed how the economic foundation of China contribute to the economic stability of this country in the region of crisis. Then, the Crisis of 1998 triggered a transition to democracy in Indonesia. It will be elaborated how the difficulties of democracy being consolidated occurred in this country. It will also be examined a crucial problem during the transition era: whether the transition to democracy strengthened integration or disintegration. Coinciding with the efforts to overcome the crisis and to build democratic institutions, Indonesia had to respond the September 11 Attack. On this issue, it will be explored the consequences of the campaign of the “War on Terror” conducted by Bush Administration to democratization in Indonesia. In the last section, it will be examined the role of Japan in the “Global War on Terrorism”. This book is the outcome of the assistance and advice of many individuals especially the colleagues of the Department of International Relations at Airlangga University Surabaya who encouraged me to publish these papers which only had been kept in my folder for several years. I would like to thank them. I would also like to record my gratitude to staff of Cakra Studi Global Strategis (CSGS) who assisted me in publishing this book. Lastly, I am grateful for the support of my family especially my wife, dr. Siti Marsiyah, who always asks me the progress of this publication.